Chemical synthesis of the 5-taurinomethyl(-2-thio)uridine modified anticodon arm of the human mitochondrial tRNALeu(UUR) and tRNALys - Leszczyńska, Grażyna; Leonczak, Piotr; Woźniak, Karolina; Małkiewicz, Andrzej (Cold Spring Harbor Laboratory Press, 2014)
5-Taurinomethyluridine (τm5U) and 5-taurinomethyl-2-thiouridine (τm5s2U) are located at the wobble position of human mitochondrial (hmt) tRNALeu(UUR) and tRNALys, respectively. Both hypermodified units restrict decoding of the third codon letter to A and G. Pathogenic mutations in the genes encoding hmt-tRNALeu(UUR) and hmt-tRNALys are responsible for the loss of the discussed modifications and, as a consequence, for the occurrence of severe mitochondrial dysfunctions (MELAS, MERRF). Synthetic oligoribonucleotides bearing modified nucleosides are a versatile tool for studying mechanisms of genetic message translation and accompanying pathologies at nucleoside resolution. In this paper, we present site-specific chemical incorporation of τm5U and τm5s2U into 17-mers related to the sequence of the anticodon arms hmt-tRNALeu(UUR) and hmttRNALys, respectively employing phosphoramidite chemistry on CPG support. Selected protecting groups for the sulfonic acid (4-(tert-butyldiphenylsilanyloxy)-2,2-dimethylbutyl) and the exoamine function (-C(O)CF3) are compatible with the blockage of the canonical monomeric units. The synthesis of τm5s2U-modified RNA fragment was performed under conditions eliminating the formation of side products of 2-thiocarbonyl group oxidation and/or oxidative desulphurization. The structure of the final oligomers was confirmed by mass spectroscopy and enzymatic cleavage data.
Keywords: human mitochondrial tRNA; modified ribonucleosides; 5-taurinomethyluridine; 5-taurinomethyl-2-thiouridine; phosphoramidite chemistry